2007
DOI: 10.1111/j.1464-410x.2007.07082.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, single‐blind, randomized crossover trial of sacral vs pudendal nerve stimulation for interstitial cystitis

Abstract: generator and patients were followed at 1, 3 and 6 months. RESULTSThe time required to place a sacral lead was 27.4 min, and a pudendal lead 19.6 min ( P = 0.039). Of the 22 patients, 17 (77%) responded and had a permanent implant placed. PNS was chosen as the better lead in 77% and SNS in 24%. The order in which the lead was stimulated had no effect on the final lead implanted and there was no 'carry-over' effect. The overall reduction in symptoms was 59% for PNS and 44% for SNS ( P = 0.05). At 6 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 14 publications
1
91
0
7
Order By: Relevance
“…Novel concepts for the treatment of CPPS are percutaneous tibial nerve stimulation, electroacupuncture, high-frequency sacral magnetic stimulation, sacral neuro-modulation (SNM), and pudendal neuromodulation [33]. Yet another type of neuromodulation is TENS, which has been established for the treatment of chronic musculoskeletal pain and may also be a valuable option in pelvic pain [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel concepts for the treatment of CPPS are percutaneous tibial nerve stimulation, electroacupuncture, high-frequency sacral magnetic stimulation, sacral neuro-modulation (SNM), and pudendal neuromodulation [33]. Yet another type of neuromodulation is TENS, which has been established for the treatment of chronic musculoskeletal pain and may also be a valuable option in pelvic pain [34].…”
Section: Discussionmentioning
confidence: 99%
“…The second aim was trying to further detect if CSRN can improve the outcome in CPPS patients with partial response to "conventional" SNM, as several articles in the treatment of CPP [9][10][11][12] reported an overall mean success rate of 60%.…”
Section: Introductionmentioning
confidence: 99%
“…kann nach erfolgloser SNM erwogen werden [43]. Peters et al [42,43] Im Vergleich zur Gruppe, die nur eine Instruktion erhielt (keine weitere Therapie).…”
Section: Pudendale Nervenstimulationunclassified
“…kann nach erfolgloser SNM erwogen werden [43]. Peters et al [42,43] Im Vergleich zur Gruppe, die nur eine Instruktion erhielt (keine weitere Therapie). PS prospektive Studie, RCT prospektive randomisierte und kontrollierte Studie ("randomized controlled trial"), NIH-CPSI "National Institutes of Health Chronic Prostatitis Symptom Index", n.s.…”
Section: Pudendale Nervenstimulationunclassified
“…[55] reported that only one of four patients with interstitial cystitis was improved after a mean follow-up of 6.5 years. A randomized crossover trial of sacral vs pudendal nerve stimulation (with the InterStim system) for interstitial cystitis indicated that overall symptom reduction with pudendal nerve stimulation might be somewhat better than with SNM (59% vs 44%; P = 0.05) [81]. Of those with a permanent IPG 13 of 17 chose the pudendal lead.…”
Section: Interstitial Cystitismentioning
confidence: 99%